GAMBARAN KARAKTERISTIK KELUARGA, POLA MAKAN DAN AKTIVITAS FISIK PADA ANAK STUNTING DI SEKOLAH DASAR NEGERI 176350 HUTAGURGUR KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN - Ris Erdima Purba; Fitri Ardiani; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The optimal growth of school age children depends on the quality and quantitiy of their nutrition. The lack of nutrition can cause disorder on the child’s body growth, such as stunting. The purpose of thisresearch is to analyze the family’s of characteristic, eating patterns, and physical activity of stunting children at SDN 176350 HutagurgurDistrict ofDoloksanggulHumbangHasundutan. This research is descriptive analysis with cross sectional design. This research includes family’s characteristic by giving questioner, counting the adequacy of macro and micro nutrition, food variety and frequency by using 24 hours food recall method and food frequency method. The height of children is measured with microtoice. The result generally shows that the height of the children is 62,8% short and 37,2% very short. The family’s characteristic mostly shows that the mother of stunting children are farmer with percentage of 88,4%. Family’s income is mostly below the minimum wage standart with percentage of 58,1%. The number of children in family with stunting child are mostly more than two children with percentage of 95,3%. The adequacy of macro and micro nutrition on stunting children is classified as lack of nutrition with percentage of energy 95,3% protein 93%,calsium 100%,phosphor 58,1%,magnesium 11,6%, zinc 97,7%, vitamin A 95,5% and vitamin C 93%. The physical activity of stunting children are mostly moderate with percentage of 51,2%. Based on the research result, expected to family especially the mother, to providea balanced nutrition intake tochildren. The school and the public health institution recomenndedto cooperate on giving nutrition counseling and also monitoring the nutrition to improve the nutrition status of school-age children . Keyword:Stunting, Characteristic of Family, Eating Patterns, Physical Activity